Percepções de profissionais sobre o uso de plataformas low-code no desenvolvimento de software - Machado, Yasmin Emily Gomes (2025)
The use of low-code platforms has been expanding in software development due to their promise of greater agility, cost reduction, and lower dependence on highly specialized teams. However, as these solutions scale, challenges emerge related to maintenance, customization, operational costs, and technological dependency. This study investigated the perceptions of professionals with experience in platforms such as OutSystems, Mendix and Salesforce, aiming to assess the long-term impacts of these tools. The research followed a quantitative and exploratory approach, through the application of a structured questionnaire to 47 professionals in the field. The results indicate a predominantly positive perception regarding productivity and scalability, while also revealing growing concerns about total cost of ownership and technical limitations in more complex scenarios. The study contributes to a more realistic understanding of the benefits and limitations of low-code platforms, offering insights for organizations considering the adoption or expansion of such solutions.